Ruang Lingkup Kebutuhan dan Kondisi Lansia - Fauziah Nasution; Aisyah Aisyah; Andini Maulia Rahma; Muthia Ramadani Safitri; Srilaili Mahfudzah (Lembaga Pengembangan Kinerja Dosen, 2025)
The elderly are an age group that experiences the aging process with various physical, mental and social changes that affect their quality of life. As the number of elderly people increases in various countries, it is important to have a clear understanding of the scope of the needs and conditions of the elderly from a social, health and economic perspective. The aim of this research is to determine the scope of the needs and conditions of the elderly. This research method uses a qualitative approach and involves literature study, data collection techniques using interview methods and literature research. This research discusses the health needs and conditions of the elderly, with a focus on medical aspects of care, including ongoing care and management of chronic conditions (such as diabetes, cholesterol and high blood pressure). Elderly people also experience several challenges, such as accessing health care facilities which is often difficult due to distance, physical limitations, or dependence on family for care. Therefore, researchers hope to provide a deeper understanding of the challenges and needs of the elderly, as well as families spending more time providing care.